Postoperative healing and behaviour when surgical swabs are applied to calf dehorning wounds. Issue 12 (26th November 2018) - Fordyce, G; McMillan, H; McGrath, N
Abstract : Objective: To assess the effect on healing and pain‐associated behaviours of covering exposed sinuses after horn amputation under extensive production conditions in northern Australia. Methods: Horned, weaned Brahman‐cross heifers (n = 50) aged approximately 6 months were alternately allocated to have their dehorning wounds either patched with a dry, non‐sterile gauze swab or left untreated. Adherence of swabs and growth rates, healing and pain‐associated behaviour were monitored for 88 days post‐surgery. Results: Half of the patches were lost by 24 h post‐surgery, with most of the rest falling off 2–6 weeks later. Patching resulted in healing 5.5 days earlier (P = 0.018). Sealing of exposed frontal sinuses occurred in most heifers within 3 weeks and full healing occurred within 13 weeks. Patching reduced haemorrhage (P < 0.01) regardless of when the patches were dislodged, prevented insect invasion of the wound and reduced the incidence of secondary infection (P < 0.01). Wound patches did not affect behaviour in the weeks following surgery. In the days after surgery, the heifers did not eat and showed a high incidence of behaviours indicating pain. Behaviour was relatively normal by 2 weeks after surgery, although the heifers avoided social interaction with other unbranded calves for 4 weeks. Conclusion: The application of gauze swabs to dehorning wounds advanced healing, reduced the incidence of haemorrhage and secondary infections, and may reduce deaths. Efficacy is expected to improve if high rates of 24‐h retention of patches can be achieved. The prolonged time to healing and the pain‐associated behaviours highlight the need for better welfare of dehorned calves through improvements in analgesia, surgical procedures and post‐surgical care.